Structural, microstructural, magnetic and electromagnetic absorption properties of spiraled multiwalled carbon nanotubes/barium hexaferrite (MWCNTs/BaFe12O19) hybrid - Rosdi, Nurshahiera; Azis, Raba’ah Syahidah; Ismail, Ismayadi; Mokhtar, Nurhidayaty; Muhammad Zulkimi, Muhammad Misbah; Mustaffa, Muhammad Syazwan (Nature Publishing Group, 2021)
Microwave absorption properties were systematically studied for synthesised barium hexaferrite (BaFe12O19) nanoparticles and spiraled multiwalled carbon nanotubes (MWCNTs) hybrid. BaFe12O19 nanoparticles were synthesised by a high energy ball milling (HEBM) followed by sintering at 1400 °C and structural, electromagnetic and microwave characteristics have been scrutinized thoroughly. The sintered powders were then used as a catalyst to synthesise spiraled MWCNTs/BaFe12O19 hybrid via the chemical vapour deposition (CVD) process. The materials were then incorporated into epoxy resin to fabricate single-layer composite structures with a thickness of 2 mm. The composite of BaFe12O19 nanoparticles showed a minimum reflection loss is − 3.58 dB and no has an absorption bandwidth while the spiraled MWCNTs/BaFe12O19 hybrid showed the highest microwave absorption of more than 99.9%, with a minimum reflection loss of − 43.99 dB and an absorption bandwidth of 2.56 GHz. This indicates that spiraled MWCNTs/BaFe12O19 hybrid is a potential microwave absorber for microwave applications in X and Ku bands.